Improving Nutritional Quality of Wheat Grain through Foliar Zinc Combined with Macronutrients. (1st January 2018) - Li, Meng; Wang, Shaoxia; Tian, Xiaohong; Huang, Yingping
Abstract : Core Ideas: Foliar N/P plus Zn caused much greater grain nutritional quality. The increased total Zn concentration after foliar applications in flour came from soluble Zn. Zinc could be applied together with N/P to increase its use in practice. Low Zn content in wheat ( Triticum aestivum L.), often associated with soil Zn deficiency, contributes to insufficient dietary intake of Zn and to widespread human Zn deficiency. Foliar Zn application has been shown to increase grain Zn concentration and bioavailability but is time and energy consuming in practice. A 2‐yr split‐plot field experiment was conducted to investigate how foliar N and P application at the early grain‐filling stage affects nutritional qualities of whole grain and flour of winter wheat (cultivar Xiaoyan 22), whether these nutrients are applied alone, as is common in practice, or are combined with Zn applications (Zn+N, Zn+P and Zn+N+P). The results showed foliar N or P applied alone had little effect on Zn concentration and bioavailability. Foliar Zn+N generally resulted in higher Zn concentration and bioavailability in whole grain and grain fractions than did foliar Zn alone, while both foliar applications containing P resulted in lower Zn concentration and bioavailability than foliar Zn alone. Foliar Zn‐containing fertilizers increased total Zn concentration in flour (averaged by 60.0% during 2012–2013 and 81.0% during 2013–2014), mainly from soluble Zn increases, while the corresponding Zn increase in bran was mainly from insoluble Zn. Amino acid concentrations in flour tended to decrease with application of foliar Zn or P alone, but increased with foliar N. Overall, our findings demonstrate foliar Zn can be co‐applied with macronutrients, especially N, to increase practicality for farmers and to improve grain and flour nutritional quality to benefit human health.